Fuzzy Control of Yaw and Roll Angles of a Simulated Helicopter Model Includes Articulated Manipulators - Hossein Sadegh Lafmejani; Hassan Zarabadipour (IAES Indonesian Section, 2015)
Fuzzy logic controller (FLC) is a heuristic method by If-Then Rules which resembles human intelligence and it is a good method for designing Non-linear control systems. In this paper, an arbitrary helicopter model includes articulated manipulators has been simulated with Matlab SimMechanics toolbox. Due to the difficulties of modeling this complex system, a fuzzy controller with simple fuzzy rules has been designed for its yaw and roll angles in order to stabilize the helicopter while it is in the presence of disturbances or its manipulators are moving for a task. Results reveal that a simple FLC can appropriately control this system.